Carcinoma of the Rectum and Rectosigmoid Colon: Role of Radiation Therapy - Reddy, Eashwer K. (1978)
Surgery is the modality of choice in curative treatment for cancer of the colon and rectum. Since a majority of the patients present advanced disease where the surgical outlook is poor, adjuvant therapy may be warranted. Clinical and experimental data demonstrate the benefits from preoperative radiation therapy and some clinical reports indicate the beneficial effects of postoperative radiotherapy. Two national studies are underway to determine the effectiveness of preoperative radiation therapy in moderate doses. A similar study is suggested to establish the effectiveness of postoperative radiation therapy. For patients who are poor surgical risks, or for a tumor which is considered to be inoperable, and in a selected group, radiation therapy can be used as a curative procedure. Advantages include eliminating the need for a permanent colostomy. In case of failure, electrocoagulation and abdominal perineal resection are still available alternatives. A modest amount of radiation therapy can afford maximum palliation with minimum discomfort to the patient. About 80-90 percent of patients with pain and bleeding and 50 percent of patients with symptomatic liver metastasis respond favorably.